Late Quaternary aeolian dynamics, pedostratigraphy and soil formation in the North European Lowlands – new findings from the Baruther ice-marginal valley - Hirsch, Florian; Spröte, Roland; Fischer, Thomas; Forman, Steven L.; Raab, Thomas; Bens, Oliver; Schneider, Anna; Hüttl, Reinhard F. (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
The construction of dunes in central Europe reflects ample sediment supply during the last deglacial hemicycle. A Quaternary inland dune complex in southern Brandenburg, Germany, was studied to determine the duration of recent pedogenesis, from two outcrops, which show buried paleosols. An integrative approach, which combined geomorphological, sedimentological, (paleo-)pedological and chronological methods was used to identify aeolian deposition events, ensuing pedogenesis and anthropogenic remobilization. At the outcrops, which were situated approximately 2 km apart from each other, in total twelve samples of the aeolian sands were dated using optically stimulated luminescence (OSL) and six using 14C dating. Although the dunes have similar morphological features, these forms have a different history of aeolian sand deposition and pedogenesis. At the older dune (Gl 1) the surface soil is a well developed Podzol, whereas soil development of the younger dune (Gl 2) is clearly in an initial state. The two dunes also differ in grain size distribution and in the presence of buried soils, thereby indicating a climatic impact on aeolian remobilization.